2017
DOI: 10.1002/lary.26608
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of Velcro versus standard twill ties following pediatric tracheotomy

Abstract: 1b Laryngoscope, 127:1996-2001, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…They have a smaller width and have a tendency to retain secretions compared to hook-and-loop cushioned ties. A randomized controlled trial [45] in 57 patients demonstrated no significant difference with respect to accidental decannulation or skin injury between traditional twill versus cushioned ties.…”
Section: Wound Carementioning
confidence: 98%
“…They have a smaller width and have a tendency to retain secretions compared to hook-and-loop cushioned ties. A randomized controlled trial [45] in 57 patients demonstrated no significant difference with respect to accidental decannulation or skin injury between traditional twill versus cushioned ties.…”
Section: Wound Carementioning
confidence: 98%
“…13 While many surgeons prefer twill ties over Velcro ties to lower this potential risk, our review demonstrates no substantial supporting evidence to justify this. Our review found that accidental decannulation is still possible with twill ties, as demonstrated by the several instances of accidental decannulation in the twill group in the study by Hart et al, 11 and actually occurred more frequently in this group than the Velcro group. In the immediate postoperative period, Velcro ties can be loosened or removed with limited manipulation by the patient and without the provider being aware.…”
Section: Discussionmentioning
confidence: 54%
“…Hart et al published a prospective randomized controlled trial comparing twill ties and Velcro ties in patients <21 years old at a single instution. 11 Patients were excluded if they underwent emergent tracheotomy or had a preexisting skin condition (epidermolysis bullosa or genetic skin disorder), and 57 patients were included (twill, n = 30; Velcro, n = 27). Mepilex lite dressings were used in all patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations